2009
DOI: 10.1177/0196859909351145
|View full text |Cite
|
Sign up to set email alerts
|

The Secret of Her Success: Oprah Winfrey and the Seductions of Self-Transformation

Abstract: This essay considers Oprah Winfrey’s rise from mere TV talk show host to global cultural icon in relationship to the rise in the 1980s and triumph in the 1990s of the neoliberal political-economic project. It argues that the expansion of Winfrey’s media enterprise and her ascent to iconic status are a product of the complex historical relationship between capitalism and the distinctly American fusion of psychology and religion captured by the term “mind cure.” Drawing on Raymond Williams’s sociology of culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…With the exception of the only North American student in the class, most reactions were overwhelmingly positive to Winfrey. Some of Peck's (2010) rationale for Winfrey's success (i.e., she provides a set of narcissistic exercises for attaining personal perfection which encourage audiences to accommodate the oppressive impact of neoliberal economic policy, rather than changing it) was then shared. It was noted that this example appeared to work very well, but some students suggested that they felt the course would be "hard".…”
Section: Cycle 1: Weeks 1 Tomentioning
confidence: 99%
“…With the exception of the only North American student in the class, most reactions were overwhelmingly positive to Winfrey. Some of Peck's (2010) rationale for Winfrey's success (i.e., she provides a set of narcissistic exercises for attaining personal perfection which encourage audiences to accommodate the oppressive impact of neoliberal economic policy, rather than changing it) was then shared. It was noted that this example appeared to work very well, but some students suggested that they felt the course would be "hard".…”
Section: Cycle 1: Weeks 1 Tomentioning
confidence: 99%
“…Although it is undeniable that the phenomenon of television has undergone several changes over the years, and countless in recent years (Aladro, 2000;Casado et al, 2023;Casetti and Odin, 2012;Correia, 2015;Eco, 1986;Faltesek et al, 2023;Filho, 2015;Lopes et al, 2023;Wolton, 1994), it seems equally undeniable that the main pillar supporting the phenomenon of daytime mass media content has remained practically intact from the beginning. From the early days of radio, there has been a constant attempt to create empathy, supported by emotional connections with the audience (Almeida, 2022;Foster and Kilby, 2023;Herzog, 1944;Hyatt, 1997;Illouz, 2003;Lourenço, 2017;Nazareth, 2016;Peck, 2010). Symbolically, daytime television still cries with those who cry and laughs with those who laugh.…”
mentioning
confidence: 99%
“… 1. See Peck (2010) for a discussion of Oprah Winfrey in relation to the neoliberal political-economic project. …”
mentioning
confidence: 99%